2011
DOI: 10.4103/0974-8520.93907
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Ashwagandha (Withania somnifera Dunal. Linn.) in the management of psychogenic erectile dysfunction

Abstract: Erectile dysfunction (ED) has been defined as the persistent inability to attain and maintain an erection sufficient to permit satisfactory sexual performance. By 2025, men with ED will be approximately 322 million, an increase of nearly 170 million men from 1995. The present study was aimed to evaluate the efficacy of Ashwagandha (Withania somnifera) in the management of psychogenic erectile dysfunction. In this study, a total of 95 patients with psychogenic erectile dysfunction satisfying the DSM IV TR diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 7 publications
2
14
0
2
Order By: Relevance
“…[33] Ashwagandha (Withania Somnifera) Ashwagandha veya "Hint ginsengi" olarak da bilinen Withania somnifera geleneksel Hint tıbbında 3000 yılı aşkın bir süredir kullanılan önemli bir bitkidir. [53][54] Gençleştirici etkisi olduğundan dolayı Hint ginsengi olarak adlandırılsa da etkileri ginsengle tamamen aynı olmayıp vücutta farklı spesifik etkiler meydana getirmektedir. [54] Vücudun fiziksel ve psikolojik durumunu iyileştirmenin yanı sıra afrodizyak, sakinleştirme, gençleştirme, yaşam uzatma, enerji verme, stresle baş etmeyi kolaylaştırma gibi etkilerinin olduğu belirtilmektedir.…”
Section: Maca (Lepidium Meyenii)unclassified
See 1 more Smart Citation
“…[33] Ashwagandha (Withania Somnifera) Ashwagandha veya "Hint ginsengi" olarak da bilinen Withania somnifera geleneksel Hint tıbbında 3000 yılı aşkın bir süredir kullanılan önemli bir bitkidir. [53][54] Gençleştirici etkisi olduğundan dolayı Hint ginsengi olarak adlandırılsa da etkileri ginsengle tamamen aynı olmayıp vücutta farklı spesifik etkiler meydana getirmektedir. [54] Vücudun fiziksel ve psikolojik durumunu iyileştirmenin yanı sıra afrodizyak, sakinleştirme, gençleştirme, yaşam uzatma, enerji verme, stresle baş etmeyi kolaylaştırma gibi etkilerinin olduğu belirtilmektedir.…”
Section: Maca (Lepidium Meyenii)unclassified
“…[54] Vücudun fiziksel ve psikolojik durumunu iyileştirmenin yanı sıra afrodizyak, sakinleştirme, gençleştirme, yaşam uzatma, enerji verme, stresle baş etmeyi kolaylaştırma gibi etkilerinin olduğu belirtilmektedir. [53,55] Günümüze kadar, Ashwagandha afrodizyak olarak çoğunlukla erkek cinsel fonksiyon bozukluğunu ve üreme yeteneğini geliştirmek için kullanılmış ve klinik çalışmalarda erkekler üzerinde yapılmıştır. [54] Kadınlar üzerinde yapılan randomize, plasebo kontrollü sadece bir pilot çalışmaya rastlanmıştır.…”
Section: Maca (Lepidium Meyenii)unclassified
“…Study design, subjects of the study, inclusion and exclusion criteria, randomization and intervention were same as that of the clinical study 6 . The study was cleared by the ethical committee of the institute.…”
Section: Methodsmentioning
confidence: 99%
“…The present laboratory findings are consistent with the clinical study which was also reported negative results. The factors like demanding and uncooperative partner, interpersonal problems or conflicts between the partners, negative personality traits, significant psychopathology and high severity of the disease etc; factors produced negative result in the clinical study 20,21 . The same factors can be attributed for negative results in the laboratory findings of the present study also.…”
Section: Serum Dhea-s Levelsmentioning
confidence: 99%
“…Kapikacchu (Mucuna prurience) is an aphrodisiac and also effective in improving the performance in men [16]. Ashwagandha is a vajikarana drug and also it is having properties like, anxiolytic, anti-depressant, anti-stress adaptogen and uplifts mood [17]. Shukra stambhana yapana vasti (medicated enema) is also found beneficial in PE [18].…”
Section: Ayurvedic Management Of Pementioning
confidence: 99%